2018
DOI: 10.1016/j.jcmg.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Atrial Strain to Predict Atrial Fibrillation After Cerebral Ischemia

Abstract: Left atrial strain adds independent and incremental predictive value to current risk-prediction models for AF following cryptogenic CVA. Further studies should examine the implications of these findings for AF monitoring or empiric anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 28 publications
4
60
2
1
Order By: Relevance
“…In a recent retrospective single-center study on 531 cryptogenic stroke patients, low atrial strain as well as global longitudinal strain of the LV showed incremental value for AF risk prediction over LA volume, LV ejection fraction and E/e' ratio [91•]. This is in line with results from another retrospective single-center study on 616 cryptogenic stroke patients [92]. In a recent small prospective single-center study with 56 cryptogenic stroke patients who had a cardiac monitor implanted for AF monitoring, low left atrial strain predicted incident AF independent of classical parameters of diastolic dysfunction, global longitudinal LV strain and cardiovascular risk factors [93].…”
Section: Cardiac Imaging For Atrial Cardiomyopathy and Prediction Of supporting
confidence: 76%
“…In a recent retrospective single-center study on 531 cryptogenic stroke patients, low atrial strain as well as global longitudinal strain of the LV showed incremental value for AF risk prediction over LA volume, LV ejection fraction and E/e' ratio [91•]. This is in line with results from another retrospective single-center study on 616 cryptogenic stroke patients [92]. In a recent small prospective single-center study with 56 cryptogenic stroke patients who had a cardiac monitor implanted for AF monitoring, low left atrial strain predicted incident AF independent of classical parameters of diastolic dysfunction, global longitudinal LV strain and cardiovascular risk factors [93].…”
Section: Cardiac Imaging For Atrial Cardiomyopathy and Prediction Of supporting
confidence: 76%
“…In that context, our finding of larger left atrial size among ESUS cases supports the concept of a thrombogenic atrial cardiomyopathy. However, the mean LAVI in our ESUS cases (approximately 33 mL/m 2 ) was within the normal range, indicating that LAVI may not be a very useful discriminator, in which case imaging biomarkers of atrial function such as left atrial strain may help distinguish between myopathic and non‐myopathic atria …”
Section: Discussionmentioning
confidence: 72%
“…The e’sr was calculated by averaging the values for peak strain rate during early diastole for the 3 apical views [22,23]. To measure LA strain, with apical 2- and 4-chamber views, the STE software algorithm was applied to the LA wall [1315]. LA stiffness was calculated as averaged E/e’ divided by LA strain (E/e’/LA strain) [13].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with conventional techniques on echocardiography including tissue Doppler imaging, speckle tracking echocardiography (STE) is more accurate for evaluating subclinical LV dysfunction [1012]. STE was also reported to enable to assess left atrial (LA) function for detecting various subclinical conditions [1315]. Few studies have used measures of echocardiographic tissue imaging, including STE-derived strain and strain rate, to assess the association of cardiac function with IVI.…”
Section: Introductionmentioning
confidence: 99%